Catalytic activity of Keggin heteropolycompounds in the Pechmann reaction - Torviso, Maria del Rosario (2008)
Different heteropolycompounds were used as catalysts in the synthesis of coumarins from phenols and ethyl acetoacetate. The H3PMo12O40 and H3PW12O40 Keggin heteropolyacids were supported on different types of silica. On the other hand, the aluminium salts of these heteropolyacids and that of the H4SiW12O40 acid were prepared. The specific surface area (SBET), and the mean pore diameter of the obtained catalysts were estimated from the adsorption isotherms of nitrogen at 77 K. Their Fourier transform infrared spectra were recorded and their acidity was determined by potentiometric titration with a solution of n-butylamine in acetonitrile. The catalytic activity using several phenols such as resorcinol, 3,5-dimethoxyphenol, a-naphtol and b-naphtol were determined. High yield of product was obtained in the case of 4-methyl-7-hydroxycoumarin (80–95%), 4-methyl-5,7-dimethoxycoumarin (60–92%) and 4-methyl-7,8-benzocoumarin (90%). However, the 4-methyl-5,6- benzocoumarin yield was low. The use of microwave radiation as power source increases the reaction yield and mainly decreases the reaction time.